Molecular docking study of the main phytochemicals of some medicinal plants used against COVID-19 by the rural population of Al-Haouz region, Morocco - Ridwane Ghanimi; Ahmed Ouhammou; Yassine El Atki; Mohamed Cherkaoui (GarVal Editorial Ltda., 2022)
Context: The infection by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is a global health emergency. The management of this crisis requires the discovery of new drugs able to cure or reduce the severity of SARS-CoV-2. Aims: To explore the medicinal plants consumed by the rural population of Al-Haouz region against the emergence of the COVID-19, and to assess in silico the main phytochemicals present in the essential oils and the extracts of these medicinal plants, as potential inhibitors of the COVID-19 main protease (Mpro). Methods: The survey was conducted through a semi-structured questionnaire among 85 respondents aged 30 years and above, in the Al-Haouz region, Morocco. AutoDock Vina, was used to assess the binding affinity of the phytochemicals to the Mpro. Results: Eleven wild medicinal species were cited; 10 belonging to the Lamiaceae family and one to the Compositae family. Thymus saturejoides Coss., Artemisia herba-alba Asso.and Mentha suaveolens Ehrh. were respectively the three most cited species during the survey. The rosmarinic acid (-7.7 kcal/mol), hesperetin (-7.2 kcal/mol), gallocatechin (-7.2 kcal/mol) and cyasterone (-7.2 kcal/mol) have shown the higher inhibitory potential against covid-19 Mpro respectively. Conclusions: In addition to their different recognized biological activities, the medicinal plants used in the Al-Haouz region have shown good inhibitory potential against SARAS-CoV-2 Mpro. Furthermore, the phytochemicals that exhibited the highest inhibitory potentials in this virtual study require further investigation in vitro and in vivo.